Inhibitory effects of benzimidazole containing new phenolic Mannich bases on human carbonic anhydrase isoforms hCA I and II. (1st November 2016) - Gul, Halise Inci; Yazici, Zehra; Tanc, Muhammet; Supuran, Claudiu T.
Abstract: New phenolic mono and bis Mannich bases incorporating benzimidazole, such as 2-(aminomethyl)-4-(1 H -benzimidazol-2-yl)phenol and 2, 6-bis(aminomethyl)-4-(1 H -benzimidazol-2-yl)phenol were synthesized starting from 4-(1 H -benzimidazol-2-yl)phenol. Amines used for the synthesis included dimethylamine, pyrrolidine, piperidine, N -methylpiperazine and morpholine. The CA inhibitory properties of these compounds were tested on the human carbonic anhydrase (CA, EC 4.2.1.1) isoforms hCA I and hCA II. These new compounds, as many phenols show moderate CA inhibitory properties.